2009
DOI: 10.3390/medicina45090094
|View full text |Cite
|
Sign up to set email alerts
|

Associations between parental skills and their attitudes toward importance to develop good oral hygiene skills in their children

Abstract: Background. For many years, poor oral hygiene and frequent consumption of sugars is known as key behavioral risk factors for oral diseases, such as dental caries and periodontal disease. Parental attitudes toward children’s oral health could be associated with their own oral health skills. We aimed to analyze associations between parental skills and attitudes toward caries development and possibilities to control positive oral health behavior in their children. Material and methods. A cross-sectional study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 20 publications
5
63
0
3
Order By: Relevance
“…In a study carried out in Lithuania, it was found that parental attitudes towards their children's oral health were significantly associated with positive parental oral health behavior [26]. Only 30% of mothers used tooth brush for their baby's mouth.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in Lithuania, it was found that parental attitudes towards their children's oral health were significantly associated with positive parental oral health behavior [26]. Only 30% of mothers used tooth brush for their baby's mouth.…”
Section: Discussionmentioning
confidence: 99%
“…In dental health research, favorable attitudes regarding dental treatment were associated with the greatest number of preventive and restorative visits (27). Moreover, parental attitudes toward their children's oral health were significantly associated with their own oral health behavior and with understanding the importance of fostering oral hygiene skills in their children (11,28).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies described the 'implementation' of other courses of action/activities not related to the theory of implementation intentions. [18] 550 parents of children of 3 and 4 years of age in Lithuania.…”
Section: Resultsmentioning
confidence: 99%
“…We found five observational studies using the Brazilian Research in Pediatric Dentistry and Integrated Clinic 2015, 15(1):345-360 TPB on the influence of the behavior of parents over their children until the age group of 5 years [12,[18][19][20][21]. The behavior and oral health conditions of parents typify the importance and value that they grant to having a good oral health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation